(untitled) (Journal of the College of Education for Women, 2019)
reader’s mind, taking the real duals in its familiarity and hostility and the symbolic imagination as well. Most of the imaginative place comes with a symbolic dimension and the artist’s characteristic ability appears so strongly in his descriptive narration; specially the (revolutionary) location such as AL QURNAWI’s tea-shop where people had gathered and set out during the 1958 Revolution in its 1st part and kept this characteristic in the following 2nd and the 3rd parts; for it was- at that time- the meeting place of those independent cultured persons in which they discussed the political situation of the whole country. In his description, Al Ahmady wrote as if he was drawing by words in order to make the suspense for coming in those places, focusing on the shades, the lights and the colours in addition to architectural designs of the places in which the events take place, are between the horizontal and vertical structure. And we stopped at Al Ahmady’s interest in general issues that busied the people mind such as the Iraqi issue in a certain era and the bond between those general issue with the individuality of the mankind in his struggle with those intruding cultural and political environment which made the narration level swaying between what is objective and individual narration; this led to the appearance and the control of the ( ego) on most of the novels narration in which the narrator became the dominant voice with such an exaggeration and inclination of the ego that finalizes the structure of the novel movement towards a certain dimension very related to the character . So we noticed that the monologue is a clear sign in the narrative structure that created such a multi open dialogues and a multi point of views of the reality associated with the characters . But as our study noticed that the characters’ dialogues based on those mutilated dialogues . As for the narrative sight in Al Ahmady’s novels we discovered that this vision is well connected because the narrator (sees with) when spoke to himself, (see from behind) and (see from outside) when he spoke about other characters; but his sight (with) is more dominant and higher in position compared to the others, so the sight wit replaces the sight from behind and the narrator became the know all. The variety of the characters in his novel made expand in the narration limits because of the great mental and political and economical differences among the characters themselves according to the goals they have which help to expand the narration limits . This narration often appears through the dialogues and the dimensions of place, time and the plot. That all contributes and participate in revealing the hidden parts of the characters and the events themselves.